PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA GURU DI MODERASI KEPEMIMPINAN KEPALA SEKOLAH DI SMK NEGERI SUB RAYON 02 KOTA SEMARANG - 11.52.02.0140, Sri Suwarni (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this study is to examine and analyze the relationship between competence, motivation and principals leadership on teacherâs performance. The research questions that are delivered are (1) does the competence affect the teacherâs performance, (2) Does motivation effect teacherâs performance, (3) Does principal leadership teacherâs performance, (4) Does principal leadership moderate the effect of competency to the teacherâs performance, (5) Does principals leadership moderate the effect of motivation to the teacherâs performance.The population of this research is SMK teachers of civil schools in Sub Rayon 02 SMK Semarang City, the sun is 294. The sample determination uses purposive sampling, the it can be got 100 respondent of sample. The methodf of data collection is usung quesioner. The data analyze technique is using double regresion.The results of this researth shows that competency does not affect the teacherâs performance, motivation affects positively & significanly the teacherâs performance . The principal leadership does not moderate the corelation of competency andteaherâs motivation to their performance Keywords: Teacherâs competency, motivation, teacherâs performance. And principalâs leadership.